2011
DOI: 10.1103/physrevb.84.235206
|View full text |Cite
|
Sign up to set email alerts
|

Low-carrier-concentration crystals of the topological insulator Bi2Te2Se

Abstract: We report the characterization of Bi 2 Te 2 Se crystals obtained by the modified Bridgman and Bridgman-Stockbarger crystal growth techniques. X-ray diffraction study confirms an ordered SeTe distribution in the inner and outer chalcogen layers, respectively, with a small amount of mixing.The crystals displaying high resistivity (> 1 Ωcm) and low carrier concentration (∼ 5×10 16 /cm 3 ) at 4 K were found in the central region of the long Bridgman-Stockbarger crystal, which we attribute to very small differences… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
225
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(250 citation statements)
references
References 22 publications
(45 reference statements)
22
225
3
Order By: Relevance
“…This discovery by Ren et al was followed by an independent report by Xiong et al, 105) who reported an even larger resistivity of 6 cm. Detailed defect chemistry in Bi 2 Te 2 Se was discussed by Jia et al 106) In passing, a tetradymite compound having a similar chalcogen-ordered structure, Sb 2 Te 2 Se, has also been confirmed to be topological, 102) but it is heavily p-type doped.…”
Section: Three-dimensional Tismentioning
confidence: 99%
“…This discovery by Ren et al was followed by an independent report by Xiong et al, 105) who reported an even larger resistivity of 6 cm. Detailed defect chemistry in Bi 2 Te 2 Se was discussed by Jia et al 106) In passing, a tetradymite compound having a similar chalcogen-ordered structure, Sb 2 Te 2 Se, has also been confirmed to be topological, 102) but it is heavily p-type doped.…”
Section: Three-dimensional Tismentioning
confidence: 99%
“…The high initial doping of the film is probably due to defects produced in growth, which is common in MBE growth of Bi 2 Se 3 films as well as bulk synthesized crystals. The mixed compound Bi 2 Te 2 Se has been found to be a more insulating material [32], and hence may respond better to our gating scheme.…”
Section: (B))mentioning
confidence: 99%
“…In contrast to compounds used in thermoelectrics, single crystals with control over the charge carrier density are needed to study the topological effects. In Bi 2 Se 3 and Bi 2 Te 3 , however, the defect chemistry is rather hard to control: Bi 2 Se 3 is n-doped due to charged Se vacancies, whereas Bi 2 Te 3 can be n-or p-doped due to antisite defects [71] and therefore the undoped samples naturally show metallic transport properties. Recently, samples of Bi 2 Te 2 Se [71,72], (Bi 1-x Sb x ) 2 Te 3 [73,74] or Bi 2 Te 1.6 S 1.4 [75] have been grown, which exhibit better bulk-insulating properties, making it possible to study the transport of surface states without the influences of the bulk.…”
Section: Filled Skutteruditesmentioning
confidence: 99%